Laclau and Mouffe : the radical democratic imaginary - Smith, Anna Marie (Routledge, 1998)
Laclau and Mouffe: The Radical Democratic Imaginary provides both a much needed overview of Laclau and Mouffe's thinking and how that thinking may be challenged and developed.